Process Mining: Measuring Key Performance Indicator Container Dwell Time - Bambang Jokonowo; Riyanarto Sarno; Siti Rochimah; Bagus Priambodo (Institute of Advanced Engineering and Science, 2019)
The issues measures duration of stay the container logistic processes at ports in developing countries is often a major problem. Therefore, a knowledge process discovery, i.e., Heuristics Miner and Fuzzy Miner, can be used to discover the insight of process by creating a process model. The container import dwell time (DT) processes can be modeled based on the event log data sources are extracted from the terminal operating system (TOS). The L* life-cycle model is used to perform the process behavior analysis steps. The results of analysis and verification show that the container import DT processes have a median duration of 5.5 days and a mean duration of 6.07 days.